International consensus on research priorities in hypospadias using a Delphi study approach - Tariq O. Abbas (11247771) (2024)
Introduction Hypospadias is a common congenital anomaly of the male genitalia that poses significant management and treatment challenges. Gaining a comprehensive understanding of priority research questions in hypospadiology will be essential to reach agreement on the optimal approach to assessment, treatment, and outcome prediction for affected patients. Methods We employed a consensus-building Delphi method to identify and prioritize research questions in the hypospadias field. Additionally, we integrated questions sourced from the artificial intelligence platform ChatGPT to capture multiple perspectives. Engaging a diverse panel of experts including clinicians, researchers, and patient advocates from across the globe, the Delphi process aimed to distill collective expertise and insights through iterative rounds of structured questionnaires and feedback. Results The analysis identified key themes in hypospadias research, covering etiology, tissue engineering, pre-clinical models, device/technology evaluation, phenotyping, surgical techniques, surgical training and postoperative outcomes. These themes highlight crucial areas for future investigation to improve understanding of hypospadias, treatment options, and patient outcomes, thereby guiding both research and clinical practice. Discussion By harnessing the collective wisdom and perspectives of multiple stakeholders, this Delphi study establishes a roadmap for prioritizing research initiatives to effectively unravel the complexities of hypospadias. Integration of ChatGPT outputs into our Delphi-based approach also outlined how future studies can harness the collective wisdom of human experts together with artificial intelligence methods. The outcomes of this novel endeavor hold promise for shaping future research agendas, informing clinical practice guidelines, and fostering multidisciplinary collaborations to drive innovation and ultimately improve outcomes for hypospadias patients worldwide. Other Information Published in: Journal of Pediatric Urology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jpurol.2024.12.005